Metabolic benefits of dietary prebiotics in human subjects: A systematic review of randomised controlled trials - Kellow, N.; Coughlan, M.; Reid, Christopher (Cambridge University Press, 2014)
© The Authors 2013. Complex relationships exist between the gut microflora and their human hosts. Emerging evidence suggests that bacterial dysbiosis within the colon may be involved in the pathogenesis of the metabolic syndrome, type 2 diabetes and CVD. The use of dietary prebiotic supplements to restore an optimal balance of intestinal flora may positively affect host metabolism, representing a potential treatment strategy for individuals with cardiometabolic disorders. The present review aimed to examine the current evidence supporting that dietary prebiotic supplementation in adults has beneficial effects on biochemical parameters associated with the development of metabolic abnormalities including obesity, glucose intolerance, dyslipidaemia, hepatic steatosis and low-grade chronic inflammation. Between January 2000 and September 2013, eight computer databases were searched for randomised controlled trials published in English. Human trials were included if at least one group received a dietary prebiotic intervention. In the present review, twenty-six randomised controlled trials involving 831 participants were included. Evidence indicated that dietary prebiotic supplementation increased self-reported feelings of satiety in healthy adults (standardised mean difference - 0.57, 95 % CI - 1.13, - 0.01). Prebiotic supplementation also significantly reduced postprandial glucose (- 0.76, 95 % CI - 1.41, - 0.12) and insulin (- 0.77, 95 % CI - 1.50, - 0.04) concentrations. The effects of dietary prebiotics on total energy intake, body weight, peptide YY and glucagon-like peptide-1 concentrations, gastric emptying times, insulin sensitivity, lipids, inflammatory markers and immune function were contradictory. Dietary prebiotic consumption was found to be associated with subjective improvements in satiety and reductions in postprandial glucose and insulin concentrations. Additional evidence is required before recommending prebiotic supplements to individuals with metabolic abnormalities. Large-scale trials of longer duration evaluating gut microbial growth and activity are required.